2010
DOI: 10.1371/journal.pone.0011853
|View full text |Cite
|
Sign up to set email alerts
|

Specification of Region-Specific Neurons Including Forebrain Glutamatergic Neurons from Human Induced Pluripotent Stem Cells

Abstract: BackgroundDirected differentiation of human induced pluripotent stem cells (hiPSC) into functional, region-specific neural cells is a key step to realizing their therapeutic promise to treat various neural disorders, which awaits detailed elucidation.Methodology/Principal FindingsWe analyzed neural differentiation from various hiPSC lines generated by others and ourselves. Although heterogeneity in efficiency of neuroepithelial (NE) cell differentiation was observed among different hiPSC lines, the NE differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 189 publications
(183 citation statements)
references
References 50 publications
6
176
1
Order By: Relevance
“…With the advent of induced pluripotent stem cell (iPSC) technology 1,3,33,34 , it is now feasible to get hESClike cells from patient fibroblasts including those with various diseases [35][36][37][38] . As shown by our group 28 as well as many others, the successful generation of neurons from iPSC has been and will continue to be a unique and useful tool for those who have long sought after human models for disease and development. In addition, several groups have shown that PSC-derived neurons can model certain aspects of the disease process 36,37,[39][40][41][42] and thus can be utilized to screen therapeutic compounds 43 .…”
Section: Discussionmentioning
confidence: 86%
“…With the advent of induced pluripotent stem cell (iPSC) technology 1,3,33,34 , it is now feasible to get hESClike cells from patient fibroblasts including those with various diseases [35][36][37][38] . As shown by our group 28 as well as many others, the successful generation of neurons from iPSC has been and will continue to be a unique and useful tool for those who have long sought after human models for disease and development. In addition, several groups have shown that PSC-derived neurons can model certain aspects of the disease process 36,37,[39][40][41][42] and thus can be utilized to screen therapeutic compounds 43 .…”
Section: Discussionmentioning
confidence: 86%
“…41 These morphogens induce robust expression of causal and ventral patterning genes in definitive NE. The expression of these genes is generally not observed until d17 45 or d28 for NC lineages. 51 However, when DNMT3B is knocked down, these regional specifier genes are precociously expressed independently of exogenous morphogens.…”
Section: Methodsmentioning
confidence: 99%
“…hESC-derived primitive NE is primarily forebrain in nature and does not robustly express region-specific markers in the absence of exogenous morphogens. 41,45 Exogenous morphogens such as retinoic acid are added to primitive NE at d10 to induce the robust expression of region-specific markers around d17, to pattern the neural precursors into region-specific neural subtypes. 45 Interestingly, we found that the knockdown of DNMT3B resulted in precocious expression of the genes that specify regional identity during neuronal differentiation by d12 without the addition of exogenous morphogens ( Fig.…”
Section: Dnmt3b Does Not Affect Early Ne Specification In Hescsmentioning
confidence: 99%
“…To prepare samples for FACS, NE cells derived from hESCs were dissociated into single cells using Accutase as described previously [24]. Cells were fixed and permeablized with ice-cold 0.1% paraformaldehyde for 10 min and 90% methanol for 30 min.…”
Section: Facs Analysismentioning
confidence: 99%
“…Spinal motor neurons, which are hard to culture and maintain from primary tissues, can be generated in large quantity from ESCs. Spinal motor neurons have been generated from induced pluripotent stem cells (iPSCs) by using a similar strategy [22][23][24], but variations in neural induction and/or motor neuron generation between different iPSC lines have been reported. Through the generation of SMA patient-specific iPSCs, recent studies revealed that the proportion of motor neurons derived from SMA iPSCs significantly decreased [25,26]; however, whether this reduction results from insufficient spinal motor neuron specification or neuronal degeneration after specification remains elusive.…”
Section: Introductionmentioning
confidence: 99%